Advancements in Modern Biotechnology for Enhanced Kojic Acid Production in the Cosmetic Industry: A Review - Herlaesa, Shofiatulfuadah Retnaningrum; Muini, Chantiara F. M.; Khaerunisa, Aulia (Jurnal Pijar Mipa, 2025)
Kojic acid (KA), a secondary metabolite from Aspergillus species, is widely used in the cosmetic industry as a skin-lightening agent, antioxidant, and anti-aging ingredient. With the growing demand for natural and effective skincare products, there is an increasing interest in sustainable and scalable KA production. Conventional fermentation methods remain limited by low yields, long incubation periods, and high costs. Advances in biotechnology now provide more efficient and reliable alternatives to overcome these challenges. This systematic review of studies published between 2020 and 2025 highlights recent developments in genetic engineering and process optimization for KA production. CRISPR/Cas9-based editing of regulatory genes such as kojR and the promoter region of kojA has improved production stability and yield, with increases reported up to 43 percent. Mutagenesis approaches using UV, gamma irradiation, microwave exposure, and atmospheric plasma have produced hyperproductive strains, with some reaching 96.5 g/L KA, representing a 293 percent increase compared with parental strains. In addition, novel regulatory proteins, including AoZFA and Aokap2, have been identified as key molecular factors controlling KA biosynthesis. Fermentation optimization also contributes significantly to efficiency. Adjustments in pH and temperature, the addition of metal ions such as Zn²⁺ and Pb²⁺, and the use of alternative substrates like sugarcane bagasse or sorghum sheaf have been shown to improve yields and reduce costs. These strategies not only increase production but also align with the demand for sustainable raw materials. Overall, integrating advanced genetic tools with optimized fermentation systems provides a strong platform for industrial-scale KA production. Modern biotechnology demonstrates clear potential to meet the requirements of the cosmetic industry while ensuring product safety, consistency, and scalability.